Penyuluhan: Pentingnya Merek Dagang Dan Sertifikasi Halal Pada Home Industri Kerupuk Cita Rasa Di Desa Pematang Berangan Kabupaten Rokan Hulu - Dari Daulay, Ulan; Riusdi, Riko (Sekolah Tinggi Agama Islam (STAI) Al- Kifayah Riau, 2025)
Micro and small enterprises in rural areas have significant potential to strengthen local economies but often face challenges in product legality. One such case involves Kerupuk Cita Rasa, a home industry owned by Aji Syafji in Pematang Berangan Village, Rokan Hulu Regency, which has yet to obtain a registered trademark and halal certification. This community service program aimed to provide integrated outreach on the importance of trademark registration and halal certification as a strategy to improve business competitiveness. The activities were carried out using a Participatory Action Research (PAR) approach through seminars, interactive discussions, document-filling simulations, and the preparation of follow-up action plans (RTL). The results showed a significant improvement in participants’ understanding of the legalization process. A total of six participants began registering their trademarks, while four others prepared the required documents for halal certification. Furthermore, the PAR approach proved effective in encouraging active participation and strong commitment to legal business development. This program is expected to serve as a replicable model for educating and empowering micro-enterprises in other areas